Information technologies for power supply dispatch control based on linguistic corpus ontologies - Morkun, V.; Kotov, I. (Natsional'nyi Hirnychyi Universytet. Naukovyi Visnyk, 2019)
Purpose. Developing methods and algorithms of smart decision support systems (DSS) and their implementation as a component of automated dispatch control systems (ADCS) in power systems.Methodology. The unitized method is applied to presenting professional ontologies. A model of signal-flow labeling is offered to control knowledge.Findings. The research results in a unitized approach to incorporating professional ontologies to build smart decision support systems and automate complex-structured objects, which is noted for implementing unity of forms of knowledge representation. All knowledge forms are described by a single model of ontologies, which enables unitizing the mechanism of representing and processing knowledge of grid modes in power systems. The mathematical apparatus of ontology representation and application is improved and differs from existing ones by the fact that it is based on fundamental forms of knowledge representation independent of subject areas. The basic model of an elementary signal-flow graph of the knowledge base is elaborated. There are introduced formalisms of the labeling parameter and functions of labeling the elementary signal-flow graph of the knowledge base. A factual knowledge base is built considering subsets of the linguistic corpus of accident elimination and prevention in power systems. A specialized thesaurus of professional terms and slang of accident elimination and prevention in power systems is built.Originality. For the first time, the research suggests a unitized approach to representing and controlling professional knowledge of dispatch emergency control based on the signal-flow graph. This enables creating efficient decision-support systems and implementing them into the current ADCS.Practical value. The authors suggest forming new ontologies of knowledge bases for the area of dispatch control modes in the power system as sensitivity matrices based on factorial mode models. There are developed integral factors of thesaurus efficiency enabling assessment of efficiency of various forms of professional knowledge representation. The operating information and control complex (OICC) which is a structural scheme of integrating the DSS into the ADCS is developed to monitor power system modes on the basis of the empirical knowledge base for mode characteristics of the power system. After generalizing the results of testing the software complex while training dispatch personnel of the power system, it can be claimed that improved professional and psychological characteristics of operating personnel, reduced intensity of dispatch failures and conditional damage because of power undersupply indicate practical relevance of applying the DSS to controlling the power system under emergency modes.